Does a competitive business strategy make firms more resilient? Evidence from the COVID‑19 pandemic - Ahsan, Tanveer; Gull, Ammar; Boubaker, Sabri; Manita, Riadh (Management international / International Management / Gestiòn Internacional)

(untitled) (HEC Montréal, 2025)
This paper examines the effects of COVID‑19 and business strategy on the performance of Chinese-listed firms. Using a sample of 2,606 Chinese non-financial listed firms over 2010-2022, we provide evidence that the COVID‑19 (business strategy) pandemic has a significant negative (positive) impact on firm performance and business strategy positively moderates the negative relationship of COVID‑19 on firm performance. We further show that firms with a proactive business strategy had better resilience during the COVID‑19 pandemic than firms with a defensive business strategy. We also find that these relationships are more pronounced for state-owned and large firms. Our results are robust to a battery of robustness tests and contribute to the growing debate on the role of business strategy during crises, offering insights to regulators and policymakers.